2017
DOI: 10.1007/s13760-017-0830-7
|View full text |Cite
|
Sign up to set email alerts
|

Unknown onset ischemic strokes in patients last-seen-well >4.5 h: differences between wake-up and daytime-unwitnessed strokes

Abstract: Patients with unknown time of stroke onset (UOS) represent around one-third of ischemic stroke patients. These are patients with wake-up stroke (WUS) or daytime-unwitnessed stroke (DUS), often presenting outside the time-window for reperfusion therapy. UOS patients presenting between 4.5 and 12 h after time of last-seen-well were included. Clinical and imaging characteristics were compared between WUS and DUS patients. Good functional outcome was defined as a modified Rankin scale of ≤2 at follow-up. Sixty-one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 35 publications
2
15
0
Order By: Relevance
“…These indicators provided a comprehensive assessment of patients during and after hospital discharge. After professional evaluation and timely follow-up, we found that WUS could not be distinguished from non-WUS by the early outcome, which was consistent with the results of a population-based study [5] and other high-quality clinical studies and randomized clinical trials [12,18,32,33].…”
Section: Discussionsupporting
confidence: 86%
“…These indicators provided a comprehensive assessment of patients during and after hospital discharge. After professional evaluation and timely follow-up, we found that WUS could not be distinguished from non-WUS by the early outcome, which was consistent with the results of a population-based study [5] and other high-quality clinical studies and randomized clinical trials [12,18,32,33].…”
Section: Discussionsupporting
confidence: 86%
“…UOS patients are unable to provide accurate symptom onset time for some reasons, for example, awakening with stroke symptoms, nonwitnessed stroke with aphasia or unconsciousness [30, 31]. They are usually considered as a contraindication for intravenous thrombolysis for the uncertain symptom onset.…”
Section: Discussionmentioning
confidence: 99%
“…In this series, up to 36% of cases of AIS had UTO. Some had stroke on awakening (wake-up stroke, WUS) and others had daytime-unwitnessed stroke 4–6. For the patients with UTO, the time of onset exceeded the therapeutic time window for intravenous tPA since the time of onset was calculated as the patient was LSN 7 8…”
Section: Discussionmentioning
confidence: 99%